2020
DOI: 10.1080/16549716.2020.1838241
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Indigenous and allopathic health practitioners in Africa and its implications for collaboration: a qualitative synthesis

Abstract: Background: There have been increasing calls for collaboration between Indigenous health practitioners (IHPs) and allopathic health practitioners (AHPs) in Africa. Despite this, very few successful systems exist to facilitate formal collaboration. Direct relationships between providers, and at a health systems level are crucial to successful collaboration, but the nature and extent of these relationships have yet to be adequately explored. Objective: To explore the relationship between IHPs and AHPs in Africa,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…These worries might be well founded because, in certain cases, traditional healthcare practitioners act unethically, endangering patient safety in the absence of regulation. Another study by Oseni and Shannon ( 2020 ) found that there was a problem with accepting the spiritual aspect of traditional health practitioners among participants. Participants in this study also indicated that there was a lack of respect and negative attitudes towards traditional healthcare practices, and this was similarly found in Van Rooyen et al (2017) who found that the lack of referral practices from allopathic to traditional healthcare practices was because allopathic health practitioners had a negative attitude towards traditional health practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…These worries might be well founded because, in certain cases, traditional healthcare practitioners act unethically, endangering patient safety in the absence of regulation. Another study by Oseni and Shannon ( 2020 ) found that there was a problem with accepting the spiritual aspect of traditional health practitioners among participants. Participants in this study also indicated that there was a lack of respect and negative attitudes towards traditional healthcare practices, and this was similarly found in Van Rooyen et al (2017) who found that the lack of referral practices from allopathic to traditional healthcare practices was because allopathic health practitioners had a negative attitude towards traditional health practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…THs in Neno strongly recommend a collaborative approach with HCWs to ensure that they are educated about danger signs that guarantee a straight referral of snakebite victims to the hospital. There is extensive literature on the integration of THs and modern medicine for various diseases and conditions, snakebites could equally benefit [ 61 , 62 ]. Further research is needed to investigate how THs in Neno can be integrated into the healthcare system, particularly in the management of snakebites.…”
Section: Discussionmentioning
confidence: 99%